The rising tide of social engineering: Trends, impacts, and multi-layered mitigation strategies - Almatarneh, Rami; Aljaidi, Mohammad; Alsarhan, Ayoub; Alshammari, Sami Aziz; Alshammari, Nayef H. (International Journal of Innovative Research and Scientific Studies, 2025)
In this paper, an analytical study explores the upcoming threat of social engineering attacks that will be presented. A comprehensive comparison among various types of social engineering, including phishing, spear phishing, vishing, pretexting, baiting, and impersonation, will be discussed in this study, highlighting their psychological manipulation tactics, increasing sophistication, and distinct operational dynamics. Historical data from 2016 to 2024 were analyzed to predict future trends and to reveal a significant rise in both the frequency and financial losses associated with these attacks. The study emphasizes the importance of human-centered mitigation strategies, particularly employee training programs combined with clear-cut security protocols, which could substantially reduce the success of attacks. In addition, in this paper, technical defenses such as domain monitoring and advanced fraud detection will be examined. The results also indicated that a multi-layered defense strategy that incorporated both technological solutions and human awareness could reduce social engineering incidents by up to 75%. Key insights from the study into the evolving landscape of cyber threats emphasized the need for continuous investment in comprehensive security measures.